Genome editing strategies for fetal hemoglobin induction in beta-hemoglobinopathies. (14th May 2020) - Demirci, Selami; Leonard, Alexis; Tisdale, John F
Abstract: Genome editing to correct a defective β-globin gene or induce fetal globin (HbF) for patients with beta-hemoglobinopathies has the potential to be a curative strategy available to all. HbF reactivation has long been an area of intense interest given the HbF inhibition of sickle hemoglobin (HbS) polymerization. Patients with HbS who also have high HbF tend to have less severe or even minimal clinical manifestations. Approaches to genetically engineer high HbF include de novo generation of naturally occurring hereditary persistence of fetal hemoglobin (HPFH) mutations, editing of transcriptional HbF repressors or their binding sites and/or regulating epigenetic intermediates controlling HbF expression. Recent preclinical and early clinical trial data show encouraging results; however, long-term follow-up is lacking, and the safety and efficacy concerns of genome editing remain.